(untitled) (Pedagogy of Higher and Secondary Education, 2007)
The article theoretically bases the role of school’s methodical work in up-growing of results of teacher’s activity in up-bringing of schoolchildren of emotional and positive attitude to study; it bases the necessity of harmonization of intellectual and emotional factors in the process of study as an important mean of an effective up rising of a methodical work in security of a qualitative education.